The Walleye War : the struggle for Ojibwe spearfishing and treaty rights - Nesper, Larry, 1951- (University of Nebraska Press, 2002)
For generations, the Ojibwe bands of northern Wisconsin have spearfished spawning walleyed pike in the springtime. The bands reserved hunting, fishing, and gathering rights on the lands that would become the northern third of Wisconsin in treaties signed with the federal government in 1837, 1842, and 1854. Those rights, however, would be ignored by the state of Wisconsin for more than a century. When a federal appeals court in 1983 upheld the bands' off-reservation rights, a deep and far-reaching conflict erupted between the Ojibwe bands and some of their non-Native neighbors.